Reconciliation in Modern Penal Policy: a Strategy for Removing Guilt and Criminal Responsibility - Umi Rozah; Heru Susetyo; Aldi Yudistira; Jaco Barkhuizen (Universitas Negeri Semarang, 2026)
The Indonesian Criminal Code (KUHP), enacted on December 6, 2022, establishes the principles of guilt and criminal responsibility in Article 36, while simultaneously expanding the scope of criminal liability beyond the requirement of the offender's fault. This provision opens the possibility of imposing criminal liability without fault (strict liability). In relation to the termination of prosecution, the KUHP also accommodates the settlement of disputes outside the court through a reconciliation mechanism. The inclusion of this provision has encouraged the researcher to examine the fundamental idea of out-of-court dispute resolution through reconciliation, and to conceptualize the ideal mechanism of reconciliation as a penal policy for eliminating guilt and criminal responsibility within the framework of modern penal policy. This study employs a normative juridical approach. The findings indicate, first, that the fundamental idea of out-of-court dispute resolution through reconciliation lies in harmonization, the protection of victims, and the avoidance of the negative impacts of imprisonment. Second, the reconciliation mechanism must be carefully considered, and this research proposes a categorization of out-of-court dispute resolution in order to provide legal certainty.